2007
DOI: 10.1590/s0073-47212007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Cranial sexual discrimination in hatchling broad-snouted caiman (Caiman latirostris)

Abstract: ABSTRACT. Broad-snouted caiman (Caiman latirostris) hatchlings present a consistent sexual dimorphism in their cranium shape and size. Male hatchlings have smaller crania than females. Using multivariate statistical analyses it is possible to discriminate sex in broadsnouted caiman hatchlings by their cranial shape with a reasonable efficiency. The understanding of sexual dimorphism of crocodilian hatchlings might be possibly improved by experimental approach considering, genetic and phenotypic variables such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
10
0
4
Order By: Relevance
“…Verdade (2000) observed sexual dimorphism in the upper region of the cranium of juveniles and adults of C. latirostris, and Piña et al (2007) obtained similar results comparing newborns 24 hr after hatching. These authors suggested that this fact may be evolutionarily related to the visual recognition of sex when individuals exhibit only the top of their heads above the surface of the water.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Verdade (2000) observed sexual dimorphism in the upper region of the cranium of juveniles and adults of C. latirostris, and Piña et al (2007) obtained similar results comparing newborns 24 hr after hatching. These authors suggested that this fact may be evolutionarily related to the visual recognition of sex when individuals exhibit only the top of their heads above the surface of the water.…”
Section: Discussionmentioning
confidence: 72%
“…Sex can affect head morphometrics even in C. latirostris hatchlings, (Piña et al, 2007). Because of this, a considerable part of the variance found among clutches of the same population might be attributed to different sex ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the black caiman ( M. niger ) was also shown to lack significant sexual dimorphism in allometric shape trajectories (Foth et al ., ). Yet, consistent sexual dimorphism has been reported in both hatchling (Piña et al ., ) and captive (Verdade, ) specimens of the broad‐snouted caiman ( Caiman latirostris ) based on linear distance measurements of the crania. In Ca.…”
Section: Discussionmentioning
confidence: 99%
“…ontogenetic variation, sexually dimorphic variation, polymorphisms) is crucial for accurate systematic, taxonomic, evolutionary, ecological, physiological and functional hypothesis of the different groups (Sudhaus and Rehfeld 1992;Wiesem€ uller et al 2003;Carpenter 2010;Porro et al 2011). Among extant crocodylians, previous studies of skull anatomy and intraspecific variation (including ontogenetic variation), evolution and functional morphology include those of Mook (1921), K€ alin (1933), Medem (1963), Iordansky (1973), Dodson (1975), Busbey (1989), Hall and Portier (1994), Monteiro and Soares (1997), Brochu (1999Brochu ( , 2001, Verdade (2000), Erickson et al (2003Erickson et al ( , 2012, McHenry et al (2006), Piña et al (2007), Wu et al (2006), Sadleir and Makovicky (2008), Platt et al (2009) and Bona and Desojo (2011). Nevertheless, lack of morphological studies and data, especially for osteology, is common to all extant South American crocodylians.…”
Section: Introductionmentioning
confidence: 99%